The Legal Politics of Regulation for Lesbian, Lesbian, Gays, Bisexuals and Transgende (LGBT) in Indonesian Law (Discourse Between Punishment and Regulation) - Anita Yuliastini; Budimansyah Budimansyah; Hj. Syarifah Arabiyah (STKIP Singkawang, 2018)
The LGBT phenomenon is a trending topic in the midst of society after the Constitutional Court has issued a Decision Number 46 / PUU-XIV / 2016 on the examination of norms on Article 284, 286 and 292 of the Criminal Code with the Decision rejecting all petition completely. LGBT is actually a classic problem that has existed as human civilization on earth. LGBT is different from other normal human beings because LGBT has a disorder in terms of sexual orientation so that such circumstances require the presence of the State to take action by criminalizing LGBT because it sees widespread impacts or otherwise violates LGBT on the basis of freedom and human rights. Political law is the activity of choosing the law that will be applied in order to achieve the purpose of the law all of which leads to the achievement of the purpose of the State with the law as a tool. This study is a normative juridical research, where the data used in this study is secondary data in the form of books, legislation, documents and other writings relating to the problems under investigation. Based on the result of the research, it is found that LGBT arrangement in law in Indonesia is a must since Indonesia is a Pancasila country with the first principle of Belief in Godhead and Country built on religious values. The constitutional juridical basis of LGBT arrangement can be seen in Pancasila as the source of all sources of law, The Introduction of the 1945 Constitution, the 1945 Constitution of Indonesian republic, Law Number 12 on 2011 concering the Formulation of Legislation which all affirm that the establishment of law in Indonesia can not be released away from the religious values adopted in Indonesia.